SELF-REPORTED MULTI-MORBIDITY WITH TUBERCULOSIS: DATA FROM THE KHYBER PAKHTUNKHWA INTEGRATED POPULATION HEALTH SURVEY (KPIPHS) IN PAKISTAN - Zia ul Haq; Saima Afaq; Farhad Ali Khattak; Sana Hussain; Sheraz Fazid; Abid Rahim; Muhammad Zeeshan Haroon; Kamran Siddiqi (Journal of Ayub Medical College Abbottabad, 2024)
Background: With the rise of non-communicable diseases (NCDs) in a country that is already facing high tuberculosis (TB) burden, TB multi-morbidity is likely to pose a significant public health challenge in Pakistan. Data were analysed to determine the prevalence of TB and explore the distribution and determinants of multi-morbidity associated with TB in the population of Khyber Pakhtunkhwa -a province of Pakistan. Methods: This is a secondary analysis of data gathered as part of the KPIPHS survey conducted in 2016-17 in both the rural and urban areas of Khyber Pakhtunkhwa, Pakistan. An interviewer-administered questionnaire was used to collect data, from adults, on demographics, education and socioeconomic status, physical and mental health, reproductive health, child health, health-related quality of life, and self-reported cardiometabolic diseases including Diabetes, hypertension, renal disorders, cardiac failure, angina, and stroke. Results: A total of 20,715 participants were recruited in the survey including 52.8% (n=10,943) males and 47.2% (n=9,772) females with a mean age of 41 (13.1) years. Data on TB status was available for a total of 14452 participants. The prevalence of TB in Khyber Pakhtunkhwa was found to be 0.49% (n=72) including an almost equal number of males and females [48% (n=34) vs 51% (n=36)], respectively. The mean age of the patients with TB was 47.5 (11.6) years. A higher proportion of people with TB had cardiometabolic diseases compared to people without TB (45.9% vs. 30.9%). Amongst the cardiometabolic disorders, self-reported hypertension (OR: 1.81, 95% CI 1.08-3.02, p=0.02), Diabetes (OR: 3.99, 95% CI 1.95-8.18, p=<0.002), and angina (OR: 3.88 95% CI 1.20-12.49, p=0.02) were positively associated with the occurrence of TB. In the adjusted analysis, only self-reported Diabetes was positively associated with the occurrence of TB (OR: 3.33, 95% CI 1.61-6.88, p=0.001). Conclusion: There is a higher burden of self-reported cardiometabolic diseases among people with TB, suggesting that this high-risk group should be screened for cardiometabolic diseases, especially Diabetes.